2012
DOI: 10.1039/c1cc16684k
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease-assisted cascaded recycling amplification for label-free detection ofDNA

Abstract: The network consisting of three kinds of unlabeled stem-loop DNA molecular beacons (MBs) is activated by target DNA in the presence of exonuclease-III (Exo-III), achieving the concept of exonuclease-assisted cascaded recycling amplification (Exo-CRA) for DNA detection with a wide dynamic range of 8 orders of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…[36][37] Due to its unique enzymatic property, Exo III is utilized to manipulate selective enzymatic digestion of probe after hybridization with target DNA to remove the target binding domain and to realize signal readout coupling with target amplification. Schematic illustration of the proposed AgNC-LMB-based method for label-free detection of sequence-specific DNA via Exo IIIaided signal amplification.…”
Section: Working Principle Of the Proposed Methodsmentioning
confidence: 99%
“…[36][37] Due to its unique enzymatic property, Exo III is utilized to manipulate selective enzymatic digestion of probe after hybridization with target DNA to remove the target binding domain and to realize signal readout coupling with target amplification. Schematic illustration of the proposed AgNC-LMB-based method for label-free detection of sequence-specific DNA via Exo IIIaided signal amplification.…”
Section: Working Principle Of the Proposed Methodsmentioning
confidence: 99%
“…Sun et al [118] reported the method for adenosine determina tion based on HCR and EASA. In some cases, the same technique was applied several times to amplify various intermediate compounds [119].…”
Section: Amplification Techniques That Provide Increase In the Analytmentioning
confidence: 99%
“…6a-c). Besides ExoIII, 117 other DNA-cleaving enzymes (such as FokI restriction endonuclease 118 and Nt.BstNBI nicking enzyme 119 ) have also been utilized for amplified bioanalysis. Besides, the release of PPIX and reset of the system can be logically controlled by AND-NOT and OR-YES logic circuits, respectively.…”
Section: Split G4 Strategymentioning
confidence: 99%